2003
DOI: 10.1002/bdd.335
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intravenous chlorzoxazone in rats with dehydration and rehydration: effects of food intakes

Abstract: The following results were obtained recently from our laboratories; in rats with 72-h water deprivation (rats with dehydration), the hepatic cytochrome P450 2E1 (CYP2E1) was three-fold induced with an increase in the mRNA. Rehydration of 48-h water-deprived rats for the next 24 h with free access of food (rats with rehydration) restored CYP2E1 level to that of control. However, rehydration of 48-h water-deprived rats for the next 24 h with limited food supply (20% of control) failed to restore the CYP2E1 level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Similar results were also obtained from other rat studies [7]. Food intake also decreased significantly in the rat model of dehydration (Tables 1, 3 and 4) and similar results were also reported from other rat studies [6,7,10,11,23,24]. The smaller body weight gain in the rat model of dehydration could be due to the lower food intake to prevent elevations in the extracellular fluid osmolarity and sodium concentration [6] in addition to water deprivation.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were also obtained from other rat studies [7]. Food intake also decreased significantly in the rat model of dehydration (Tables 1, 3 and 4) and similar results were also reported from other rat studies [6,7,10,11,23,24]. The smaller body weight gain in the rat model of dehydration could be due to the lower food intake to prevent elevations in the extracellular fluid osmolarity and sodium concentration [6] in addition to water deprivation.…”
Section: Discussionsupporting
confidence: 92%
“…This indicated that DA-7867 was mainly reabsorbed in the renal tubules for both groups of rats. The renal extraction ratios of DA-7867 (Cl r of DA-7867/ kidney plasma flow rate; only for urinary excretion of unchanged DA-7867) were estimated based on Cl r (Table 2), hematocrit [25] and kidney blood flow rate in control rats, 36.8 ml/min/kg [35], and in the rat model of dehydration [36]. After 8 days of water deprivation in rats, the renal blood flow rate reduced by 65% [36].…”
Section: Discussionmentioning
confidence: 99%
“…Water was not supplied during the experimental period in the rat model of dehydration, since this will cause partial rehydration in the rat model of dehydration. It was reported that supplying water in the rat model of dehydration (rehydration) causes pharmacokinetic changes of chlorzoxazone [25] and tissue distribution changes of gentimicin in rats [14] compared with those in the rat model of dehydration. Approximately a 0.12 ml aliquot of blood was collected via the carotid artery at 0 (to serve as a control), 1 (at the end of the infusion), 5,30,60,90,120,180,240,360,480,720,960 and 1440 min after intravenous administration of DA-7867.…”
Section: Intravenous Studymentioning
confidence: 99%
“…The 0.9% NaCl-injectable solution was infused at rates of 0.3-1.5 ml/min to control the urine flow rate. Note that this experiment could not be performed in the rat model of dehydration, because rehydration of 48 h water-deprived rats for the next 24 h caused partial restoration of the total area under the plasma concentration-time curve from time zero to time infinity (AUC) of intravenous chlorzoxazone (metabolized to 6-hydroxychlorzoxazone via CYP2E1 in rats) in rat model of water deprivation to the controls [16].…”
Section: Ratsmentioning
confidence: 99%